The Role of Bhabinkamtibmas in Preventing the Crime of Motor Vehicle Theft at the Bandung Sumur Police Department - Septiani Dewanti (Advances in Police Science Research Journal, 2021)
This research is motivated by the increasing number of motor vehicle theft crimes in Sumur Bandung District. The high level of community activity in Sumur Bandung sub-district makes the criminal acts that occur are high as well. And the pattern of prevention that is prioritized by the Police is more acceptable to the public than the pattern of repression or repression. This research uses a qualitative approach with descriptive research type. Data collection techniques by interview, observation, and review of documents. There are primary and secondary data sources and the theories used to analyze are role theory and management theory. The results of the study found that the role of Bhabinkamtibmas in preventing criminal acts of curanmor was carried out through guidance given to Tibmas, Swakarsa, Polmas, and Potmas. Meanwhile, the efforts made by Bhabinkamtibmas are through the Friday Tour and the Three Pillars program. There are factors that influence Bhabinkamtibmas in carrying out its duties, namely internal factors consisting of human resource factors, facilities and infrastructure factors, and budget factors, while external factors come from the community itself. Based on the discussion of the research, the writer provides suggestions to the leadership to conduct analysis and evaluation to Bhabinkamtibmas personnel and has standardization for the assessment of Bhabinkamtibmas members, emphasizes providing material to the public regarding motor vehicle theft, improving suggestions and infrastructure owned by the Bandung Sumur Police, and give rewards and punishments to members of Bhabinkamtibmas as motivation to work.